Association of Haemoglobin and Serum Albumin Level with Short Term Surgical Complications in Operable Gastric Cancer (Journal of Surgical Sciences, 2025)
Background: Gastric cancer is the fifth most common cause of cancer-related death in Bangladesh. Curative resection remains the main modality of its successful treatment but the rate of postoperative complications is still high. Besides surgical factors, patient’s clinicopathological characteristics influence complications. This study was aimed to find out the association of the patients’ haemoglobin and serum albumin levels with short-term surgical complications in operable gastric cancer.  Methodology: Following convenience sampling, 32 patients of operable gastric cancer who underwent gastrectomy in the Department of General Surgery, Bangabandhu Sheikh Mujib Medical University, from July 2019 to June 2020 were observed for their clinicopathological characteristics and postoperative complications. Data were analyzed with SPSS version 23 and Chi-square (÷2) test was done to find out the association of complications with the patients’ haemoglobin and serum albumin levels.Result: Out of the 32 patients 12 (37.50%) patients developed complications. Thirty days mortality was 6.30%. Preoperative low Hb level (Male < 13 gm/dl & female < 11.50 gm/dl), low albumin level (< 3.50 gm/dl)) and postoperative lowest Hb level (< 9 gm/dl) were significantly associated with complications (p-value 0.018, 0.003 and